2017
DOI: 10.1111/fcsr.12239
|View full text |Cite
|
Sign up to set email alerts
|

All Hands on Deck: Research Needed to Examine the Educator Shortage in Family and Consumer Sciences

Abstract: The purpose of this article was to present the current status of the Family and Consumer Science (FCS) educator shortage and the “Say Yes to FCS” national initiative to recruit FCS educators. Explaining the educator shortage contextually by exploring issues and trends over time, highlights the backdrop against which the current educator recruitment initiative coalesced. Emergent findings from the Say Yes initiative demonstrate a few important points: (i) comprehensive data collection at the state and federal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Both these factors have implications on patient safety as well as the nurses’ capacity to detect complications early [ 51 ]. In conclusion, burnout and turnover among healthcare staff are not just an organizational challenge or a topic for economic analysis but a global issue with real-world effects in terms of quality of health care [ 23 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both these factors have implications on patient safety as well as the nurses’ capacity to detect complications early [ 51 ]. In conclusion, burnout and turnover among healthcare staff are not just an organizational challenge or a topic for economic analysis but a global issue with real-world effects in terms of quality of health care [ 23 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Housing education, for instance, has long suffered from a reduced presence in school‐based curricula (Brewer, 1986). Family and consumer sciences education is often one of the first to succumb to resource constraints within secondary curricula and university programs across the U.S. (Duncan et al., 2017). Preparing today's youth for future challenges will require integrating housing‐related content into more traditional or “core” educational resources (Barnum, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of empirical research to understand and apply the conceptual frameworks that comprise the intellectual foundation of the profession is concerning for advancing and sustaining the profession. Scholars, including and Duncan et al (2017), have identified challenges associated with the declining number of FCS research professionals. Another contributing factor is the high number of unpublished dissertations.…”
Section: M Pl Icat Ion S a N D L I M I Tat Ion Smentioning
confidence: 99%